Epitaxial Growth of High Curie-Temperature Ge1-xMnx quantum dots on Si(001) by auto-assembly - Phuong, Luong Thi Kim; Nguyen, An Manh (Communications in Physics, 2014)
We report on successful growth of epitaxial and high Curie-temperature Ge1-xMnx quantum dots on Si (001) substrates using the auto-assembled approach. By reducing the growth temperature down to 400 °C, we show that the Mn diffusion into the Si substrate can be neglected. No indication of secondary phases or clusters was observed. Ge1-xMnx quantum dots were found to be epitaxial and perfectly coherent to the Si substrate. We also observe ferromagnetic ordering in quantum dots at a temperature higher 320 K. It is believed that single-crystalline quantum dots exhibiting a high Curie temperature are potential candidates for spin injection at temperatures higher than room temperature.